PROSPECTS OF RUSSIAN BANKING SYSTEM IN GLOBALIZATION - Viktor Aleksandrovich Bondarenko (Вестник Северо-Кавказского федерального университета)
The main tendencies and factors of globalization of a banking system are characterized. The assessment of influence of the foreign capital on dynamics of the banking sector of the country is carried out. The effect from Russia's accession to the World Trade Organization and OECD is analysed. Observance of requirements of the Basel agreement III concerning standards of sufficiency of the capital and liquidity of the credit organizations of Russia is considered.